Evaluation of the Functional Suitability of Carboxylate Chlorin e6 Derivatives for Use in Radionuclide Diagnostics; Pharmaceutics; Vol. 18, iss. 1 - Larkina M. S. Mariya Sergeevna; Demina A. Anastasia; Suvorov N. Nikita; Ostroverkhov P. Petr; Plotnikov E. V. Evgeny Vladimirovich; Varvashenya R. N. Ruslan Nikolaevich; Bodenko V. V. Vitalina Vasiljevna; Yanovich G. Gleb; Prach A. A. Anastasiya Aleksandrovna; Pogorilyy V. Viktor; Tikhonov S. Sergey; Popov A. Alexander; et al. (2026, 2026)
Radionuclide-based molecular imaging modalities are active and developing areas of functional and molecular diagnosis. Among the radionuclides used for SPECT imaging in oncology, 99mTc is a leading candidate for radiolabeling. At present, a sufficient number of complexons for 99mTc have been described; however, the development of effective delivery systems for this isotope to the area of interest is a complex research task. The use of tumor-targeting molecules as carriers for radioactive tracers is an effective strategy that has enabled the development of many novel radiopharmaceuticals for cancer imaging. Background: To date, a number of studies have shown tumorotropicity of tetrapyrrole compounds to tumor tissues, in particular derivatives of natural chlorophyll A. Methods: Purification was performed using solid-phase extraction. Assessment of radiochemical yield and purity was performed via radio-ITLC. The in vitro tumor cell accumulation was assessed using SKOV-3 and A-431 cell lines. Dose-dependent biodistribution was evaluated in Nu/J mice bearing epidermoid carcinoma (A-431) xenografts. Results: In this work, we obtained complexes with 99mTc based on water-soluble carboxylate chlorin e6 derivatives in order to evaluate their potential for use as SPECT radiopharmaceuticals. We performed radiolabelling optimization of a series of the novel chlorins and primary preclinical studies, including an assessment of the effect of their lipophilicity and charge on tumor uptake. Conclusions: Modification of the periphery of the chlorin macrocycle with chelating groups allows for complexing a wide range of metals, including 99mTc, which can be used for targeted delivery of the radionuclide to the area of interest